Implementation of School-Based Management to Optimize Character Education in Primary School - Nurhidayati, Nurhidayati; Anjarini, Titi; Ratnaningsih, Arum (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2024)
This study aims to describe and explore the implementation of School-Based Management (SBM) in optimizing character education at the primary school level. The research explicitly examines how schools plan, implement, and evaluate character education programs within the SBM framework, and identifies the supporting and inhibiting factors that influence their effectiveness. A descriptive qualitative approach with a multi-site study design was employed, involving three primary schools in Purworejo Regency: SDN Purworejo 01, SDN Purworejo 03, and SDN Purworejo 05. The research sites were selected purposively based on the schools’ formal integration of character education into their School Development Plans (RKS). Data were collected through in-depth interviews with principals, teachers, and school committee members; classroom and school culture observations; and document analysis, including RKS documents, character education programs, and operational guidelines related to school management. Data were analyzed using the Miles and Huberman interactive model, consisting of data reduction, data display, and conclusion drawing. The findings indicate that SBM supports character education through school autonomy in designing student-oriented character programs, visionary principal leadership that promotes a positive school culture, teachers’ and school committees’ active participation in habituation activities, and the integration of character values into thematic learning. The study also identifies several inhibiting factors, including limited monitoring of character programs, inconsistent parental reinforcement, and teachers’ administrative workload. These results highlight the importance of strengthening SBM practices by enhancing leadership capacity, improving family involvement, and developing operational, measurable SOPs to support sustainable character education in primary schools.